Modernisasi Pesantren: Kritik Nurcholish Madjid Terhadap Pendidikan Islam Tradisional - YASMADI (Ciputat Press, 2002)
Modernisasi Pesantren: Kritik Nurcholish Madjid Terhadap Pendidikan Islam Tradisional